Voyage to the Philippines - Chan, Cecilia (Linguae et Litterae; 2008, 2010)
November 15 – At noon, we sailed around the islands of Bucutua, Tongkil, Balanguigui, Sinisa. Soon, we were sailing off Sulu Island, its high mountains covered with vast prairies of cogon surrounded by forests. Although I had a good pair of binoculars, I could only see a few houses. We passed in front of Paticol, where Spanish troops landed on February 22, 1876. At six o’clock, we anchored on the northwestern part of the island.